The progress of reason as an end of social rationality in Kant? - Weber, Sulamith (Studia Kantiana, 2023)
The essay investigates whether from a Kantian perspective, we can gain insights for a deeper understanding of the concept of social rationality. One strength of Kant's approach is to distinguish from a concept of mere formal rationality an emphatic account of reason as a faculty of human beings, anchored in human nature and destined to be fully developed. By distinguishing two dimensions in which the progress of reason is seen by Kant as the highest aim of nature – first, as ultimate end of nature, then, as final end of nature –, we can achieve an extended concept of social rationality, denoting not only a means for the promotion of the progress of reason but also the heuristic idea of a social reason itself, a kind of social reasonableness.